2016
DOI: 10.1007/s10902-016-9823-0
|View full text |Cite
|
Sign up to set email alerts
|

Demystification of the Relationship Between Psychopathy and Happiness

Abstract: Recent findings have provided evidence for a negative correlation between psychopathy and happiness. In order to determine if this correlation is generalizable to all subtypes of psychopathy, participants from the community (N = 572) were recruited to examine happiness-related features among males and females by psychopathic subtypes. Examination of the Fearless-Dominance (PPI-I) and Impulsive-Antisociality (PPI-II) subscales of the Psychopathic Personality Inventory-Short Form provided evidence for two distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 67 publications
2
17
0
2
Order By: Relevance
“…Successful psychopaths were initially defined as individuals possessing core psychopathic traits (such as lack of empathy and emotional detachment), but also possessing adaptive traits, such as social charm, low neuroticism, and stress/anxiety resilience [ 10 12 ]. Although the inclusion of the aforementioned adaptive components as key structures of psychopathy is highly debatable, numerous studies provided evidence of a relationship between an increase of psychopathic traits and adaptive traits [ 13 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful psychopaths were initially defined as individuals possessing core psychopathic traits (such as lack of empathy and emotional detachment), but also possessing adaptive traits, such as social charm, low neuroticism, and stress/anxiety resilience [ 10 12 ]. Although the inclusion of the aforementioned adaptive components as key structures of psychopathy is highly debatable, numerous studies provided evidence of a relationship between an increase of psychopathic traits and adaptive traits [ 13 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, PPI-I focuses on three adaptive characteristics, namely social charm, stress and anxiety immunity, and fearlessness. Although the relationship between PPI-I and psychopathy is highly debated [ 4 , 6 , 24 , 25 ], results nevertheless suggest that high levels of PPI-I are associated with numerous adaptive traits, such as lower provoked violence [ 17 ], higher levels of self-esteem and stable happiness [ 22 , 26 ], and emotional stability [ 20 ]. Similarly to the PPI, the Triarchic Psychopathy Measure (TriPM) includes a component, namely boldness, measuring the adaptive side of psychopathy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…levels of Meanness (equivalent of primary psychopathy) and Boldness, but not in Disinhibition (equivalent of secondary psychopathy). The relationship between psychopathy and gender is highly unclear, as some studies found differences across all dimensions of psychopathy (Durand & Plata, 2017;Poy, Segarra, Esteller, López, & Moltó, 2014), others found differences in only portions of the components of psychopathy (Durand, 2016;Miller, Gaughan, & Pryor, 2008), while others did not observe any relationship between gender and psychopathy (Miller, Watts, & Jones, 2011). Additionally, the covariate effect of IM was replicated on all components of the TriPM.…”
Section: Discussionmentioning
confidence: 99%
“…A previous research supported that high levels of narcissism was positively associated with life satisfaction and happiness, while psychopathy and Machiavellianism were negatively or uncorrelated with both variables (Aghababaei & Blachnio, 2015). Another study focusing on psychopathy and well-being supported that psychopathic traits related to social dominance was positively associated with happiness, presence of a meaning in life, personal growth, and hope, while psychopathic traits associated with impulsive antisociality were negatively associated with the aforementioned The Quantitative Methods for Psychology r12 variables (Durand, 2018a).…”
Section: Introductionmentioning
confidence: 84%